Menganalisis dan Mengidentifikasi Kesulitan Belajar Siswa ADHD di SMA Islam SHAFTA Surabaya - Aulia Adyatma Robbi Siswanto; Oktafia Setia Ayu Ramadhani; Fitri Adelia Najwa; Junivan; Kaniati Amalia (CV Putra Publisher, 2024)
Attention Deficit Hyperactivity Disorder (ADHD) is a neurodevelopmental disorder that affects children's learning patterns, characterized by inattention, hyperactivity and impulsivity. These symptoms can cause significant learning difficulties, impacting academic performance and social relationships. Understanding the challenges that students with ADHD experience is crucial for Educators and policy makers to create effective strategies. This research analyzes the learning difficulties of students with ADHD at SHAFTA Islamic High School, aiming to identify the challenges in the classroom and provide insights for appropriate educational tactics and provide motivation for everyone that providing the right support to ADHD students who experience learning difficulties can help these students to get the potential they have. The method used is qualitative data obtained through interviews with educators. This study emphasizes the importance of implementing tailored educational strategies and creating an inclusive learning environment, so that the population can improve the experience and academic outcomes of students with ADHD.